Generative AI in Education: Challenges and Opportunities - Lopes, A. L. (2nd International Conference on Education Research, 2025)
The rapid rise of generative artificial intelligence (AI) has transformed the educational landscape, creating both unprecedented opportunities and significant challenges for higher education. This presentation explores the role of generative AI as a cognitive collaborator in teaching and learning, highlighting its potential to enhance productivity, creativity, and personalized learning experiences for both educators and students. It also examines the inherent risks, including overreliance, reduced critical thinking, data privacy concerns, and academic integrity issues. Through practical examples and institutional initiatives at Iscte, the talk discusses strategies for developing generative AI literacy among teachers and students, integrating AI tools ethically and effectively into educational practices, and rethinking pedagogical models to foster authentic learning in the age of AI.